Viktimisasi Perkotaan: Moral Panic Korban Penggusuran Kampung Bayam Sebagai Akibat Pembangunan Jakarta International Stadium - Christiani Karisma Michavadeny Merentek (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
This study uses a literature study research method. Researchers collected data from journals, news articles, books, regulatory laws and literature reviews. The theoretical concepts used are the theory of Victimization and the theory of Panic Morale. There are 3 dimensions that cause victimization to occur, namely, Target Vulnerability, Target Gratifiability and Target Antagonism. The results of the study show that the lack of attention to victims of crime will have a wider impact than expected, even this absence will give rise to criminogens, namely conditions in which the public lacks confidence in crime prevention carried out by law enforcers and creates a feeling of insecurity and not infrequently will lead to revenge. to other people or certain groups.